Hubungan antara Pengalaman Kerja dan Motivasi dengan Kinerja Pegawai di Dinas Kelautan, Perikanan, dan Ketahanan Pangan - Tria Aprilia; Komariyah Komariyah (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to analyze the relationship between work experience and motivation with employee performance at the Department of Marine Affairs, Fisheries and Food Security. Optimal employee performance is very important to achieve organizational goals and effectiveness, especially in the government sector related to marine and fisheries. This study adopted a quantitative approach with a survey method, using questionnaires distributed to employees at the agency. Data analysis was conducted using descriptive and inferential statistical techniques to evaluate the effect of work experience and motivation on employee performance. The results showed that both work experience and motivation significantly affect employee performance. Work experience contributes to improving skills and knowledge that have an impact on work efficiency, while motivation plays a role in increasing employee enthusiasm and dedication. This study concludes that the development of training programs and motivational initiatives can improve employee performance at the Department of Marine Affairs, Fisheries and Food Security, and recommends strategies to optimize both factors.